2007
DOI: 10.1016/j.brainres.2007.03.067
|View full text |Cite
|
Sign up to set email alerts
|

Secretory PLA2-IIA and ROS generation in peripheral mitochondria are critical for neuronal death

Abstract: In this study the role of mitochondrial secretory PLA2-IIA in glutamate-induced cell death in cultured cerebellar granule neurons has been investigated. Inhibition of secretory PLA2-IIA blocked glutamate-induced cell death. Since PLA2 may generate reactive oxygen species (ROS), we have investigated ROS production, detected as dihydrorhodamine 123 oxidation and nitrotyrosine modifications of proteins, following glutamate treatment in the absence or presence of an inhibitor of secretory PLA2-IIA. There was an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 129 publications
(135 reference statements)
0
20
0
Order By: Relevance
“…Mitochondria were loaded with the nonfluorescent dye MitoTracker CM-H2XROS, which selectively accumulates within mitochondria and subsequently oxidized to a fluorescent chromophore, as repeatedly demonstrated in the past. [20][21][22] Free LipAc did not reduce the fluorescence of the redox-sensitive probe at 1 mm concentration (Figure 4 A). At higher concentrations (10 mm), LipAc had significantly elevated endogenous ROS levels after 12 h. In contrast, reversibly targeted LipAc (revMitoLipAc) protected mitochondria from endogenous ROS at 1 mm and 10 mm concentrations.…”
mentioning
confidence: 84%
“…Mitochondria were loaded with the nonfluorescent dye MitoTracker CM-H2XROS, which selectively accumulates within mitochondria and subsequently oxidized to a fluorescent chromophore, as repeatedly demonstrated in the past. [20][21][22] Free LipAc did not reduce the fluorescence of the redox-sensitive probe at 1 mm concentration (Figure 4 A). At higher concentrations (10 mm), LipAc had significantly elevated endogenous ROS levels after 12 h. In contrast, reversibly targeted LipAc (revMitoLipAc) protected mitochondria from endogenous ROS at 1 mm and 10 mm concentrations.…”
mentioning
confidence: 84%
“…Commercially available c(2NapA)LS(2NapA)R (sPLA 2 -IIA inhibitor I) protected cerebellar granule neuron death induced by glutamate and inhibited ROS production in peripheral neuronal mitochondria [105]. A recent study also demonstrated that this pentapeptide could abolish NMDAinduced increase in PLA 2 activity and apoptotic cell death of cortical primary neurons [19].…”
Section: Native Peptidesmentioning
confidence: 97%
“…However, the presence of sPLA 2 in intracellular compartments of neural cells [9,48] suggests that endogenous enzymes might also participate in apoptotic cell death. Indeed, inhibition of GIIA by a cell permeable specific inhibitor could reduce glutamate-induced death of cerebellar granule neurons [105]. In addition, GIIA was also involved in the generation of ROS in peripheral mitochondria.…”
Section: Involvement Of Spla 2 In Neurological Diseasesmentioning
confidence: 99%
“…This revealed that ROS was at the upstream of activation of p38 MAPK. Given that oxidative stress arising from activation of NADPH oxidase has been reported to be associated with neurodegenerative disorders [Mathisen et al, 2007;Sun et al, 2007], the effect of DPI (inhibitor of NADPH oxidase) on p38 MAPK activation was assessed. Co-incubation of DPI with PLA 2 or BPB-PLA 2 abolished p38 MAPK activation and upregulation of Fas and FasL (Fig.…”
Section: P38 Mapk Activation and Upregulation Of Fas And Fasl Are Evomentioning
confidence: 99%